2019
DOI: 10.1021/acsearthspacechem.9b00177
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate and Carboxylate Suppress the Formation of ClNO2 at Atmospheric Interfaces

Abstract: We report measurements of the nitryl chloride (ClNO 2 ) branching fraction following reactive uptake of N 2 O 5 to mixed organic and inorganic solutions representative of atmospheric interfaces. For sodium chloride containing solutions, mixed with either sodium sulfate (Na 2 SO 4 ) or sodium acetate (NaAc), the ClNO 2 branching fraction (Φ ClNO 2 ) is suppressed relative to a sodium chloride only solution. In the case of the sulfate-chloride solution, Φ ClNO 2 is reduced from 0.85 ± 0.03 (0.5 M NaCl) to 0.32 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(89 citation statements)
references
References 37 publications
(110 reference statements)
9
77
3
Order By: Relevance
“…5 . A recent laboratory study (Staudt et al, 2019) has reported that sulfate and acetate can suppress ClNO 2 for Cl − -containing solutions, but such a sulfate suppression effect was not observed in our results. Further studies are needed to identify and quantify these effects for better parameterizing the heterogeneous ClNO 2 production.…”
Section: Observation-based Empirical Parameterization Of γ N 2 Ocontrasting
confidence: 97%
See 3 more Smart Citations
“…5 . A recent laboratory study (Staudt et al, 2019) has reported that sulfate and acetate can suppress ClNO 2 for Cl − -containing solutions, but such a sulfate suppression effect was not observed in our results. Further studies are needed to identify and quantify these effects for better parameterizing the heterogeneous ClNO 2 production.…”
Section: Observation-based Empirical Parameterization Of γ N 2 Ocontrasting
confidence: 97%
“…The two cities of Tai'an and Jinan (the capital of Shandong Province) are 15 and 60 km to the south and north, respectively. N 2 O 5 and ClNO 2 were measured using an iodide-adduct chemical ionization mass spectrometer (CIMS; THS Instru-ment, Atlanta), which has been deployed in several field campaigns Tham et al, 2016;Yun et al, 2018). The related trace gases (O 3 ,NO,and NO 2 ,etc.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BT09 parameterization excluding 190 chloride effects (yellow markers) gives much better agreement, with more values located in the range within a factor of 2, though the γ N2O5 was still overpredicted in most of the studies in North America (Bertram et al, 2009b;Riedel et al,2012;McDuffie et al, 2018a) except for Boulder (Wagner et al, 2013). The improvement indicates that the efficiency of chloride in competing for the H 2 ONO 2 + intermediate and the effects on N 2 O 5 uptake on ambient aerosols might be overestimated, possibly due to the existence of other nucleophiles competing with Cl - (McDuffie et al, 2018b;Staudt et al, 2019), or different mixing 195 states of particle and non-uniform distribution of available chlorine in the aerosols.…”
Section: Comparison To Parameterizationsmentioning
confidence: 96%